Tissue engineering of adipose tissue with biodegradable biomaterials for soft tissue reconstruction Tissue Engineering von Fettgewebe mittels bioabbaubaren Biomaterialien zur Weichteildefektdeckung - Klein, Silvan; Aung, Thiha; Haas, Robert Michael; Medved, Fabian; Schiller, Stefan M.; Felthaus, Oliver; Dolderer, Jürgen H. (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2018)
Soft tissue defects resulting from injuries, tumor resection, congenital anomalies or chronic wounds pose a great challenge to reconstructive surgery. The current gold standard in therapy of such defects is the tissue transplantation in terms of free or local flaps. Unfortunately, donor site morbidity remains a considerable risk of flap surgery. Therefore, tissue engineering of autologous vascularized long term stable adipose tissue constructs could enrich the therapeutic possibilities of soft tissue defects. De novo adipose tissue growing requires fundamental knowledge about this kind of tissue and its synthesis, closely linked to angiogenesis. Bioresorbable biomaterials (scaffolds) are of crucial importance for adipose tissue engineering. Simulation or replacement of extracellular matrix for tissue growth by scaffold application requires a profound understanding of cell-matrix interactions. A proper biomaterial should be capable of supporting cell adherence, proliferation and differentiation. Important features are biocompatibility and resorption without toxic metabolites. In this review, various scaffold materials are discussed and novel achievements are presented. Persisting problems of de novo adipose tissue formation are high resorption rates and small tissue volumes of adipose constructs. Adipose tissue formation in a tissue engineering chamber is an additional possibility for in vivo tissue engineering. Recent studies proof that long term stable de novo adipose tissue formation of clinically relevant tissue volumes is possible. This method, in our opinion, has the potential to improve therapeutic strategies of soft tissue defects significantly.
CRIS-Team Scopus Importer:2024-12-11
Keywords: adipose tissue; biomaterials; reconstructive surgery; soft tissue defect; tissue engineering